An ingested metallic wire migrating from stomach to pancreas treated by laparoscopic surgery: A case report - Hao, Fulong; Feng, Qingbo; Li, Jiaxin; Wu, Hong (Frontiers in Surgery, 2023)
Introduction Foreign bodies inside the pancreas are rare and usually occur after the ingestion of sharp objects such as a fish bone, a sewing needle, or a toothpick. Furthermore, an ingested metallic wire migrating from stomach to pancreas is very rare. Case Presentation We report a 36-year-old woman who was admitted to our hospital with “3-day history of dull progressive epigastric pain.” Computed tomography of the abdomen revealed a linear, high-density body between the stomach wall and the pancreas. During the operation, a linear, hard, metallic wire was found in the adhesive tissue between the gastric antrum and the pancreatic body. The operation was uneventful, and the patient recovered well. Conclusion The case of a foreign body inside the pancreas caused by a metallic wire is very rare. Radiological examinations play a vital role in the diagnosis of metallic wire ingestion. Metallic wire ingestion can be treated with laparoscopic surgery, both technically and safely.